DIMENSIONS OF SPIRITUALITY AND MEANING OF LIFE IN MUSLIM WOMEN WEARING HIJAB IN INDONESIA: DIMENSIONS OF SPIRITUALITY AND MEANING OF LIFE IN MUSLIM WOMEN USING HIJAB IN INDONESIA - Junaidin, Junaidin; Latief, Nurulsani S. Abd.; Kahar, Amalia S.J. (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The existence of the meaning of life for Muslim women in Indonesia who wear the hijab is influenced by the dimensions of spirituality. Therefore, this study aimed to examine the prediction of the dimensions of spirituality toward the meaning of life in Muslim women who wear hijab. The data were collected by using the spirituality dimension scale and the meaning of life scale with the alpha cronbach value of each variable was 0.850 and 0.861. The research subjects were women wearing hijab, amounting to 347 people with an average age were 18-20 years. The data were analyzed by using simple regression analysis with significance level of 0.05. The results of this study indicated that the dimension of spirituality affects the meaning of life for Muslim women (wearing hijab) in Indonesia.